(2-Ketulosonyl)onate 2, 3-O-thionocarbonate donors for the synthesis of KO and KDO α-glycosides and a one-pot glycosylation method for 2-keto acid donors. Issue 16 (8th July 2020) - Mong, Kwok-Kong Tony; Pradhan, Tapan Kumar; Chiu, Cheng-Hsin; Hung, Wei-Cheng; Chen, Chao-Ju; Wang, Yi-Fang
Abstract : Bifunctional (2-ketulosonyl)onate thionocarbonates are effective donors for the synthesis of KO and KDO α-glycosides with perfect control in stereoselectivity. Abstract : We report a short synthetic strategy for direct preparation of (2-ketulosonyl)onate donors. These donors feature a cyclic thionocarbonate group at the C2 and C3 positions, which plays a multitude of chemical roles. It protects the C2 and C3 hydroxyls during building block preparation. In glycosylation, the thionocarbonate can be activated by a sulfenylating promoter and serves as a leaving group. Because of its β-configuration, it also plays the role of a stereo-directing group during the formation of the α-glycosidic bond. In addition, the thionocarbonate donors can couple with thioglycoside acceptors. This orthogonal property was used for the development of the first one-pot glycosylation method for 2-keto acid sugars.